Revalidation of Yphthimoides inornata (Hayward, 1962 (Lepidoptera: Nymphalidae: Satyrinae: Satyrini: Euptychiina) based on morphological and molecular data with description of the immature stages - Piovesan, Mônica; Orlandin, Elton; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2022)
Yphthimoides inornata (Hayward, 1962) stat. rev., currently regarded as a nomen dubium and synonym of Yphthimoides yphthima (C. Felder & R. Felder, 1867) has its status revalidated based on morphological characters and the DNA barcode. Images of the male and female, including their genitalia, information on the distribution, habitat, and immature stages are provided.